Analisis Kinerja Routing Protokol AODV pada Jaringan VANET (Studi Kasus : Kecamatan Cakranegara) - Muhamad Zaelani Syahrir Ramadhan; I Wayan Agus Arimbawa; Moh Ali Albar (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
Vehicular Ad-hoc Network is the concept of a subset of Mobile Ad-Hoc Networks (MANET) where vehicles act as nodes on the network. Protocol routing is very influential on the performance of the network to deal with challenges related to the rapidly changing network topology. This study analyze the routing performance of the AODV protocol on vanet networks in the district of Cakranegara by analyzing performance results using end to end delay parameters, packet delivery ratio (PDR), throughput, and routing overhead. The average Maximum value at end to end delay is 940.577 ms while the minimum value is 50,065 ms, and the average speed value decreases delay at speed 50 to 30 km / h by 78,314 ms and from 30 to 10 km / hour decreased by 102,827 ms. The maximum average value in the packet delivery ratio is 84.75% while the minimum value is 55.33%, and the average speed value decreases the ratio at the speed of 50 to 30 km / hour by 7.26% and from 30 to 10 km / h has increased by 10.39%. The average maximum value at throughput is 69,553 Kbps while the minimum value is 10.06 Kbps, and the average speed value decreases throughput at speeds of 50 to 30 km / h by 1,065 Kbps and from 30 to 10 km / h decreases amounting to 0.658 Kbps. The average Maximum value on routing overhead is 37,311 bytes while the minimum value is 7,439 bytes, and the average speed value increases at a speed of 50 to 30 km / hour by 1,321 Bytes and from 30 to 10 km / hour decreases by 5,453 Bytes. Key words: AODV, VANET, Routing Protocols, SUMO, NS2.